RISK FACTORS’ IDENTIFICATION ACCORDING TO THE DEVELOPMENT OF HEALTHCARE ASSOCIATED INFECTIONS AND MORTALITY BY USING COMPETING MODELS AT TIMONE UNIVERSITY HOSPITAL’S ICU - Ahmed Haddadi; Mohamed Lemdani; Hervet Hubert (European Scientific Journal, ESJ, 2014)
Whatever their specialty (surgical, medical or both), intensive care units have to take care of patients due to life-threatening conditions as the result of one or even several organ failures. They register the highest mortality rates (Sheng WH, 2005), and the highest numbers of nosocomial infections (Mathieu LM, 2001). There have been numerous studies intended to evaluate the risk factors and the consequences of these infections in ICU (Intensive Care Unit) patients. However the analyses in most of these studies disregard the fact that there are additional competing events such as discharge or death. The study is retrospective. It is based on a total of 250 patients of at least 16 years old and having spent at least 72 hours in ICU in the Timone University Hospital. Several risk factors were studied in two distinct competitive risk models. In the first model, we investigated the nosocomial infections risk factors with such a competing risk model as discharge (patients dead or living). The mortality risk factors were studied in the second model in which the patient being discharged faces the mortality competing risk. 46 patients developed at least one nosocomial episode, and 65 died. The nosocomial infection objectified risk factors are: CVC (causespecific hazard ratio = 9.08; 95% CI 1.10 to 75.20), chronic renal failure (8.99; 95% CI 1.92 to 42.12) and tracheotomy (2.69; 95% CI 1.45 to 5.01). Cancer (2.69; 95% CI 1.48 to 4.89), transplant (7.30; 95% CI 1.83 to 29.19) and the SOFA score (1.36; 95% CI 1.23 to 1.51) are the target factors for mortality risk. Of all the documented scores in the present study the SOFA is the score with the highest predictive capacity as far as death risk is concerned. On the other hand, even if the nosocomial infection alters the event discharge, its impact on mortality is not completely established